Handbook of pharmaceutical excipients - Sheskey, Paul J.; Cook, Walter G.; Cable, Colin G. (Pharmaceutical Press ; American Pharmacists Association, 2017)
The Handbook of Pharmaceutical Excipients is internationally recognised as the authoritative source of information on pharmaceutical excipients giving a comprehensive guide to uses, properties and safety.